1995
DOI: 10.1161/01.res.76.6.927
|View full text |Cite
|
Sign up to set email alerts
|

Contraction-Induced Cell Wounding and Release of Fibroblast Growth Factor in Heart

Abstract: The heart hypertrophies in response to certain forms of increased mechanical load, but it is not understood how, at the molecular level, the mechanical stimulus of increased load is transduced into a cell growth response. One possibility is that mechanical stress provokes the release of myocyte-derived autocrine growth factors. Two such candidate growth factors, acidic and basic fibroblast growth factor (aFGF and bFGF, respectively), are released via mechanically induced disruptions of the cell plasma membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
161
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(164 citation statements)
references
References 38 publications
2
161
0
1
Order By: Relevance
“…Sublethal membrane wounding and release of cytosolic bFGF without cell necrosis have also been documented in vivo after strenuous or eccentric contraction of normal and dystrophic muscle or in contraction-induced cell wounding in the heart. 29,30 It is possible, although to date not formally proven, that the release of bFGF is particularly important in skeletal muscle and heart and is under the control of a physiological process. We have observed that levels of released bFGF are proportionally elevated in the conditioned medium of a myoblast cell The number of vessels staining positive in gastrocnemius muscle sections were counted under a Zeiss microscope (magnification ×200) and expressed in number per mm 2 (field surface = 0.74 mm 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sublethal membrane wounding and release of cytosolic bFGF without cell necrosis have also been documented in vivo after strenuous or eccentric contraction of normal and dystrophic muscle or in contraction-induced cell wounding in the heart. 29,30 It is possible, although to date not formally proven, that the release of bFGF is particularly important in skeletal muscle and heart and is under the control of a physiological process. We have observed that levels of released bFGF are proportionally elevated in the conditioned medium of a myoblast cell The number of vessels staining positive in gastrocnemius muscle sections were counted under a Zeiss microscope (magnification ×200) and expressed in number per mm 2 (field surface = 0.74 mm 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the intact heart, we have documented increased release by ELISA of both bFGF and aFGF in the perfusate of adult rat hearts retrogradely perfused for 5 min ex vivo in a Langendorff preparation with a physiologic saline solution containing 10 Ϫ7 M isoproterenol (60). In confluent serum-starved neonatal rat ventricular myocytes as well as adult rat ventricular myocytes, addition of exogenous bFGF or aFGF induced activation of MAP kinase kinase (MEKs) as well as both 42-and 44-kD isotypes of MAPK (ERK2/ERK1) (10).…”
Section: Discussionmentioning
confidence: 99%
“…If entry of the oxidative environment is important in membrane resealing in many cell types, then modulation of the extracellular oxidative state could have therapeutic implications in a number of tissues where compromised membrane repair may be involved, including skeletal and cardiac muscles. 17,18 Additionally, the involvement of a ubiquitous binding target like PS in MG53 function could indicate that MG53 may be able to function in cell types other than muscle. If it can function in non-muscle cell types, MG53 could have significant therapeutic implications.…”
Section: Article Addendummentioning
confidence: 99%